The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s13075-017-1411-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of medial meniscal extrusion with medial tibial osteophyte distance detected by T2 mapping MRI in patients with early-stage knee osteoarthritis

Abstract: BackgroundMedial meniscal extrusion (MME) is associated with progression of medial knee osteoarthritis (OA), but no or little information is available for relationships between MME and osteophytes, which are found in cartilage and bone parts. Because of the limitation in detectability of the cartilage part of osteophytes by radiography or conventional magnetic resonance imaging (MRI), the rate of development and size of osteophytes appear to have been underestimated. Because T2 mapping MRI may enable us to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 43 publications
3
76
0
Order By: Relevance
“…8 MME was measured before HTO and at 6-week follow-up (study protocol) through use of magnetic resonance imaging (MRI) by 2 experienced radiologists, both of whom were blinded to patient information. The measurements were made on the MRI coronal view of the medial meniscus showing the best image of the tibial eminence, in accordance with the techniques proposed by Hada et al 14 and Roos et al 22 The intraclass correlation coefficient (ICC) was used for interrater and intrarater reliability analyses. 20 To assess intrarater reliability, 1 radiologist repeated all measurements 2 weeks later.…”
Section: Mri and Radiographic Evaluationmentioning
confidence: 99%
“…8 MME was measured before HTO and at 6-week follow-up (study protocol) through use of magnetic resonance imaging (MRI) by 2 experienced radiologists, both of whom were blinded to patient information. The measurements were made on the MRI coronal view of the medial meniscus showing the best image of the tibial eminence, in accordance with the techniques proposed by Hada et al 14 and Roos et al 22 The intraclass correlation coefficient (ICC) was used for interrater and intrarater reliability analyses. 20 To assess intrarater reliability, 1 radiologist repeated all measurements 2 weeks later.…”
Section: Mri and Radiographic Evaluationmentioning
confidence: 99%
“…As described above, there are many potential therapeutic targets for osteoarthritis. Recently, a clinical study demonstrated the presence of hypertrophic chondrocytes and osteophytes in articular cartilage of early stage of patients with knee osteoarthritis [116]. Importantly, this study also showed that these pathological changes cause medial meniscal extrusion and consequent dislocation of the meniscus [116].…”
Section: Discussionmentioning
confidence: 63%
“…Recently, a clinical study demonstrated the presence of hypertrophic chondrocytes and osteophytes in articular cartilage of early stage of patients with knee osteoarthritis [116]. Importantly, this study also showed that these pathological changes cause medial meniscal extrusion and consequent dislocation of the meniscus [116]. Presumably, this process is different from the normal regulation of endochondral ossification, and unidentified molecular mechanisms are involved in the underlying pathological events.…”
Section: Discussionmentioning
confidence: 75%
“…Hada found that osteophytes in the medial tibial and/or femoral sites were present in 98% of patients with knee OA (49/50 cases). 30 Although the molecular mechanisms of osteophyte formation remain unknown, experimental studies using animal models have shown that osteophytes develop as a result of repeated mechanical stresses or soluble growth factors. 31,32 The causal relationship and the underlying mechanisms need to be examined by future longitudinal studies and experimental researches.…”
Section: Re Sultsmentioning
confidence: 99%